L'insertion du CECR en Albanie - Eldina Nasufi (Recherches en didactique des langues et des cultures)
In this article, we aim to describe the attempts made to introduce the Common European Framework of Reference for Languages in Albania. With this purpose in mind, we will try to establish whether the CEFR can really be applied in the practice of Albanian teachers, and to identify the achievements and the problems teachers face in relation to this important issue in the field of language teaching/learning.We will concentrate especially on the teaching/learning of French language at all levels of teaching and at the same time we will focus on the case of the Alliance Française, in Tirana where a significant number of people of different age groups learn the French language and prepare to initiate their studies in France.